Epistemic modesty, ostentatiousness and the uncertainties of epigenetics: on the knowledge machinery of (social) science. Issue 1 (21st April 2016) - Pickersgill, Martyn
Abstract: Epigenetic processes are garnering attention in the social sciences, where some scholars assert their importance for theorizing social life. I engage with such ideas here by drawing on interviews with leading bioscientists. To begin with, I underscore the (productive) uncertainties of those working in and around epigenetics; I describe these as a manifestation of 'epistemic modesty', and suggest that dissensus helps to propel biomedical innovation. Then, drawing on the concept of 'alien science', I detail some researchers' ambivalences regarding the notion of 'transgenerational inheritance'; their dissatisfaction with the (public) communication practices of other scientists (situated in what I term a regime of 'epistemic ostentatiousness'); and the challenges faced when moderating societal discussion of epigenetics in ways that expand excitement whilst deflating (what researchers regard as) unrealistic expectations. The paper concludes with reflections on the knowledge machinery of the (social) sciences, and employs the study data to interrogate sociological engagements with epigenetics.